(untitled) (Research, Society and Development, 2022)
With the growing development of the Brazilian financial market, the interest of small investors was visible, from the year 2019 and until june 2020 the entry of individual investors in the stock exchange had a growth of 174.7% reaching 2,824,239 people according to B3. Despite this significant number, only 3% of the population that has some investment product owns shares of publicly traded companies, given this information is really the niche market that can be exploited. In most cases this small percentage is due to the profile of the Brazilian investor, which can be termed as conservative. Even investors who own a stock portfolio have a low value intended for this type of capital market product. This fear can be attributed to the lack of time to study the market and even by not having knowledge of it, another point that we have to take into account is the emotional and psychological insecurity of gains and losses in the small investor’s portfolio, tied to poor risk management. Given the scenario, we advise some stock portfolios by reducing their risks or optimizing their returns by Markowitz’s method that uses statistical and rational methods. It became apparent during the study the cost benefit and assertiveness of the same. For the development of this work, the Design Thinking method was used.